Effects of hot isostatic pressing on the elastic modulus and tensile properties of 316L parts made by powder bed laser fusion - Nicholas Lavery (Materials Science and Engineering: A, 2017)
The microstructure and mechanical properties of 316 L steel have been examined for parts built by a powder bed laser fusion process, which uses a laser to melt and build parts additively on a layer by layer basis.Relative density and porosity determined using various experimental techniques were correlated against laser energy density. Based on porosity sizes, morphology and distributions, the porosity was seen to transition between an irregular, highly directional porosity at the low laser energy density and a smaller, more rounded and randomly distributed porosity at higher laser energy density, thought to be caused by keyhole melting. In both cases, the porosity was reduced by hot isostatic pressing (HIP).High throughput ultrasound based measurements were used to calculate elasticity properties and show that the lower porosities from builds with higher energy densities have higher elasticity moduli in accordance with empirical relationships, and hot isostatic pressing improves the elasticity properties to levels associated with wrought/rolled 316 L. However, even with hot isostatic pressing the best properties were obtained from samples with the lowest porosity in the as-built condition.A finite element stress analysis based on the porosity microstructures was undertaken, to understand the effect of pore size distributions and morphology on the Young's modulus. Over 1–5% porosity range angular porosity was found to reduce the Young's modulus by 5% more than rounded porosity. Experimentally measured Young's moduli for samples treated by HIP were closer to the rounded trends than the as-built samples, which were closer to angular trends.Tensile tests on specimens produced at optimised machine parameters displayed a high degree of anisotropy in the build direction and test variability for as-built parts, especially between vertical and horizontal build directions. The as-built properties were generally found to have a higher yield stress, but lower upper tensile strength and elongation than published data for wrought/hot-rolled plate 316 L. The hot isostatically pressed parts showed a homogenisation of the properties across build directions and properties much more akin to those of wrought/hot-rolled 316 L, with an increase in elongation and upper tensile strength, and a reduction in yield over the as-built samples.